Efficacy of pillar implants to reduce snoring and daytime sleepiness - Khasawneh, Laith (Future Sci OA, 2021)
OBJECTIVE: To measure the efficacy of pillar implants in reducing snoring. MATERIALS AND METHODS: A total of 30 adult patients who underwent pillar implants were assessed preoperatively and at 1, 3, 6 and 12 months after the implantation. Improvement was measured using snoring frequency, visual analog scale for snoring loudness, and Epworth sleepiness scale for daytime sleepiness. RESULTS: The mean snoring frequency, loudness and Epworth score were reduced from 6.9, 9.2 and 7.4 at the baseline to 5, 5.9 and 5.6, respectively, at 12 months postoperatively (all p < 0.03). The partial implant extrusion rate was 6.7%. CONCLUSION: We suggest that a pillar implant procedure should be considered before proceeding to more morbid surgeries in patients with snoring and daytime sleepiness.